Selenium and zinc: Two key players against cadmium-induced neuronal toxicity. (April 2018) - Branca, Jacopo J.V.; Morucci, Gabriele; Maresca, Mario; Tenci, Barbara; Cascella, Roberta; Paternostro, Ferdinando; Ghelardini, Carla; Gulisano, Massimo; Di Cesare Mannelli, Lorenzo; Pacini, Alessandra
Abstract: Cadmium (Cd), a worldwide occupational pollutant, is an extremely toxic heavy metal, capable of damaging several organs, including the brain. Its toxicity has been related to neurodegenerative diseases such as Alzheimer's and Parkinson's diseases. The neurotoxic potential of Cd has been attributed to the changes induced in the brain enzyme network involved in counteracting oxidative stress. On the other hand, it is also known that trace elements, such as zinc (Zn) and selenium (Se), required for optimal brain functions, appears to have beneficial effects on the prevention of Cd intoxication. Based on this protective effect of Zn and Se, we aimed to investigate whether these elements could protect neuronal cells from Cd-induced excitotoxicity. The experiments, firstly carried out on SH-SY5Y catecholaminergic neuroblastoma cell line, demonstrated that the treatment with 10 μM cadmium chloride (CdCl2 ) for 24 h caused significant modifications both in terms of oxidative stress and neuronal sprouting, triggered by endoplasmic reticulum (ER) stress. The evaluation of the effectiveness of 50 μM of zinc chloride (ZnCl2 ) and 100 nM sodium selenite (Na2 SeO3 ) treatments showed that both elements were able to attenuate the Cd-dependent neurotoxicity. However, considering that following induction with retinoic acid (RA), the neuroblastoma cell line undergoes differentiation into a cholinergic neurons, our second aim was to verify the zinc and selenium efficacy also in this neuronal phenotype. Our data clearly demonstrated that, while zinc played a crucial role on neuroprotection against Cd-induced neurotoxicity independently from the cellular phenotype, selenium is ineffective in differentiated cholinergic cells, supporting the notion that the molecular events occurring in differentiated SH-SY5Y cells are critical for the response to specific stimuli. Highlights: Cd inhibits neurite outgrowth, induces oxidative stress, leads to neuronal apoptosis. Zn protects undifferentiated and RA differentiated SH-SY5Y neurons from Cd toxicity. Se is effective against Cd-neurotoxicity only in undifferentiated SH-SY5Y cells.